Cognitive impairment in fall-related studies in Parkinson’s disease - Domingos, Josefa M. M. (2022)
© 2015 – IOS Press and the authors. All rights reserved. This article is published online with Open Access and distributed under the terms of the Creative Commons Attribution Non-Commercial License.